The Level and Associated Factors Of Knowledge, Attitude and Practice of Blood Donation among Health Science Students of Addis Ababa University - Misganaw, Chalachew; Tenkir, Meaza; Deresea, Andualem; Tesfaye, Megdelawit; Tessema, Tesfalem Teshome; Taye, Hawult (International Journal of Medical and Health Sciences Research, 2014)
Introduction: Blood can save millions of life. Blood is the cure, and- man is only source of that cure. The 2012 world blood donor day campaign is "Every blood donor is a hero" focuses on the idea that every one of us can become a hero by donating blood. The percentage of blood collected from voluntary Blood donors and the average annual blood collection rate in Ethiopia are extremely low. Objective: To assess knowledge, attitude, and practice of blood donation and associated factors among health science students in Addis Ababa University. Method: A quantitative institution based cross-sectional study design was used to conduct the survey on May 2014 among health science students in Addis Ababa University. There were a total of 384 respondents selected from six departments of the College of Health Sciences in the university. Stratified sampling technique followed by systematic sampling was applied to select respondents. A pretested self-administered questionnaire was used to collect data. Data will be cleaned, edited, coded and entered on SPSS version 16. Descriptive statistics was applied to describe variables. An analysis of logistic regressions for identifying associated factors was done. A significance level of less than or equal to 0.05 was considered significant. Result: More than half of the participants, 206 (53.6%) were males and the age range of most of respondents, (90%) were from 19-24 years. Fifty six percent of respondents were studying medicine. Three hundred twenty one (83.7 %) and 63(16.4%) of respondents have high and low level of knowledge regarding blood donation. Increased year of study and being students in the department of medicine and nursing increased the odds of level of knowledge of respondents on blood donation. Being age > 25 years increased odds of knowledge [AOR (95% CI) =5.092 (1.1, 24.2)]. One third, 123(32%) of respondents have unfavorable attitude towards blood donation. Being male increased odds of favorable attitude [AOR (95% CI) =2.2 (1.4, 3.6)]. Less than one quarter, 90 (23.4%) have ever donated blood. Among these, 38(42.2%) of them were a regular donors. Being male increased odds of practice [AOR (95% CI) =3.9 (1.4, 10.8)] and being age >25 increased odds of practice [AOR (95% CI) =6.5 (1.6, 26.9). Conclusion and recommendations The level of knowledge on blood donation is high, however, significant number of students in this study have unfavorable attitude towards blood donation. Practice of blood donation is good. In this study, being male, age > 25 and increased year of study and department have significant association. The university in collaboration with Red Cross society should increase and strengthen clubs. Moreover, clubs in the university should organize different events to build students attitude positively and to increase the number of blood donors.